Ewolucja systemu zarządzania turystyką i produktem turystycznym w regionach jako element poprawy konkurencyjności rynkowej - Gryszel, Piotr (Evolution of Management System of Tourism and of Tourist Product in Regions as an Element of Market Competitiveness Improvement, 2008)
The objective of the herby article is to point to changes in tourism management of tourist attractive areas. The article presents evolution in tourism management of tourist destinations starting from the model of joint tourism promotion, moving on to cooperation aiming at the construction of a tourist product and finishing with the marketing system of a destination management. It is also indicated that it is more efficient to create and manage a tourist product in a tourist destination than in a defined tourist region, which is characterized by its predefined boundaries. The Organization (Institution) for Destination Management is referred to as the main coordinator of such activities, and its advantages are pointed to over a classical regional or local tourist organization. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 87-94